A 1st-trimester combined screening test in pregnant women of advanced maternal age in a Chinese population. (February 2015) - Pan, M.; Han, J.; Yang, X.; Zhen, L.; Liao, C.; Li, D.Z.
Abstract The purpose of this study was to evaluate the performance of the 1st-trimester combined screening test for trisomy 21 in different maternal age groups in a Chinese population. In this retrospective study, data on the 1st-trimester combined screening test (maternal age, fetal nuchal translucency, free β-human chorionic gonadotrophin, pregnancy-associated plasma protein-A) were analysed. The study population of 17, 556 pregnant women was subdivided into three groups according to maternal age: 16, 113 were < 35 years of age; 1, 228 were 35–39 years of age; and 215 were ≥ 40 years of age. The detection and false-positive rates of the 1st-trimester screening test for trisomy 21 or trisomy 18 in the three groups of women were 89.5 and 1.7%; 90.9 and 6.8%; and 100 and 22.3%, respectively. With increasing maternal age, the odds of being affected given a positive result (OAPR) were increased. The balance between the detection rate and false-positive rate of the 1st-trimester combined screening test is more favourable in women < 36 years with comparable OAPR. Although the false-positive rate increases with increasing maternal age, the performance of the 1st-trimester combined screening test in women ≥ 35 years is more effective than screening based on maternal age alone.